THE IMPLEMENTATION OF COLLABORATIVE LEARNING STRATEGY IN TEACHING READING COMPREHENSION TO STUDENTS OF MADRASAH ARIFAH GOWA - Nur Jihan Faatihah; Ahmad Talib; Geminastiti Sakkir (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The objective of this research is to find out whether or not Collaborative Learning Strategy (CLS) affects students in their reading comprehension. This study was pre-experimental and involved one group pre-test and post-test. This research took place at Madrasah Arifah Gowa in the 2020/2021 academic year. The population of this research was first-grade students. The researcher used the total sampling technique in selecting the samples which consisted of 26 students as respondents. This research used a quantitative method design. The researcher used to read test as the research instrument. The technique data collection was pre-test and post-test. The results of students’ reading scores from pre-test to post-test demonstrate a significant difference. It is found that Sig.(2-tailed) is 0.000 < from 0.05. The results show that the mean score of pretests is 63.65 with a standard deviation of 7.81, while the mean score of post-tests is 76.34 with a standard deviation of 9.54. It means that there is an effect of the implementation of the Collaborative Learning Strategy in teaching reading comprehension to students of Madrasah Arifah Gowa.